AI-Assisted Learning on Students’ Grammar: Improvement andLearning Experience - Friska Adila; Harpain (Jurnal Ragam Pengabdian, 2026)
This study aims to investigate the use of AI-assisted learning with authentic Sustainable Development Goals (SDGs)-based materials to improve students’ grammar and learning experiences. The study employed an explanatory sequential mixed-methods design. Data were collected through a grammar pretest and posttest to assess students’ understanding of the Simple Past Tense and a Likert-scale questionnaire to explore students’ learning experiences. The participants were 36 eleventh-grade students at SMA Persada Bandar Lampung. Data analysis included paired sample t-test analysis and N-Gain score calculation to measure grammar improvement, as well as descriptive analysis of students’ responses. The results indicated that students’ grammar achievement improved after the implementation of AI- assisted learning. Students reported positive learning experiences and perceived AI and SDGs-based materials as helpful and engaging, although some interaction difficulties still happened. The findings suggest that AI- assisted learning with authentic materials had potential to enhance grammar learning. However for optimal outcomes, longer implementation of the learning was needed.